Business Strategies in Contexts of High Uncertainty: Challenges of an Aluminum Producer in Argentina (1970-2001) - Rougier, Marcelo (2012)
This paper examines the business strategies of the firm Aluminio Argentino (Aluar) since its inception in 1970 to the 2001 economic crisis. The commissioning of the plant was made possible by the tremendous support of the State and his performance coincided with a period of great macroeconomic instability and sharp reduction in domestic demand, deal with the aggravation of aninternational market marked by the recession which was held almost until the nineties. The study also illustrates the strategies of the business once the regulatory framework that gave rise disappeared and the company faced a strong competitive shock.